Spiral Tube Decorations: a Thousand Years of Tradition - Riina Rammo (EXARC, 2016)
An overview of finds, their regional spread and significance though the ages. The spiral tubes are made of an alloy that consists of copper supplemented mainly with zinc and/or tin (Rammo, Ratas 2015, table 1). The outer diameter of the spiral tubes usually range from 2.5 to 5 mm. Woollen and linen threads as well as horse hairs, were used to join spiral tubes into decorations.